Aramid insulation paper with aging resistance and high thermal stability and preparation method thereof

By adopting the structure of composite outer layer and inner layer of aramid insulating paper, using aminating modification treatment and nanotitanium dioxide reinforcement materials, the problem of performance attenuation of existing aramid insulating paper in high temperature environments is solved, and the high thermal stability and anti-aging performance are significantly improved.

CN119686167APending Publication Date: 2025-03-25ELECTRIC POWER RES INST CHINA SOUTHERN POWER GRID CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510164187.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing aramid insulating paper has significantly attenuated mechanical properties and insulation properties under long-term high temperature and strong oxidation atmosphere, limiting its wide application under harsh conditions.

Method used

Aramid insulating paper with anti-aging and high thermal stability composed of composite outer layer and aramid inner layer, the composite outer layer includes unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nanocomposite slurry. The aramid inner layer includes unmodified meta-aramid fiber, which enhances the interface binding force of the fibers by amino modification and provides excellent heat resistance and electrical insulation properties through nanotitanium dioxide reinforcement materials.

Benefits of technology

It significantly improves the anti-aging and thermal stability of aramid insulating paper, enhances the overall mechanical and electrical properties of the paper, and avoids the performance attenuation of traditional insulating paper in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119686167A_ABST
    Figure CN119686167A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-performance insulating materials, and discloses anti-aging and high-thermal-stability aramid insulating paper and a preparation method thereof.Active amino functional groups are introduced to the surfaces of aramid fibers through amination modification treatment, and the interface bonding force between the fibers and filler and other fibers is enhanced. According to the present invention, with the introduction of the nanometer titanium dioxide reinforcing material, the dispersibility and the uniformity of the fiber are improved, the traditional fiber agglomeration problem is avoided, the overall mechanical property of the paper is enhanced, especially the interlayer bonding strength and the tear resistance are enhanced, and the introduction of the nanometer titanium dioxide reinforcing material provides the excellent heat resistance and the excellent electrical insulation property for the insulation paper. In the treatment process of the filler, an SDS dispersing agent is added to further stabilize the dispersion of the filler. Through ultrasonic dispersion treatment, uniform distribution of nano titanium dioxide in the slurry is ensured, the interface bonding force between the filler and the amino-modified aramid fiber is further enhanced, the thermal expansion coefficient of the paper is reduced, and the dimensional stability of the paper is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance insulating materials, and in particular to an aramid insulating paper with anti-aging and high thermal stability and a preparation method thereof. Background Art

[0002] With the rapid development of new energy electric vehicles, high-speed railways, and high-frequency and high-voltage power equipment, higher requirements are placed on the performance of insulating materials. These materials need to maintain excellent mechanical properties and insulation properties in high temperature, high humidity and long-term working environments. However, although the existing aramid insulation paper has good mechanical strength and temperature resistance, its mechanical and insulation properties will be significantly attenuated under long-term high temperature and strong oxidizing atmosphere, limiting its wide application under harsh conditions. This attenuation is mainly due to the breakage of the polymer chain of aramid fiber during thermal aging, resulting in damage to the microstructure of the material, thereby affecting the long-term reliability of the insulation paper. Therefore, it is urgent to develop a new type of aramid insulation paper with both high thermal stability and significant anti-aging properties to meet the needs of the development of modern electrical equipment.

[0003] Aramid insulation paper, as a high-performance insulating material based on aromatic polyamide fibers, is widely used in traditional electrical equipment such as transformers, motors and generators. Traditional aramid insulation paper is mainly prepared by wet papermaking process with aramid short fibers and aramid cellulose microfibers as the main raw materials. Although the material exhibits excellent thermal stability, mechanical strength and electrical properties, its limitations gradually emerge when dealing with the requirements of modern electrical equipment for high power density, miniaturization and long life. On the one hand, the surface chemical inertness of aramid fibers is strong, and it is difficult to form a strong interface bond with other materials such as fillers or fiber matrix, which makes the internal bonding force of the composite material insufficient and reduces its overall mechanical properties; on the other hand, in multi-layer stacking or large thickness application scenarios, problems such as delamination or cracks are prone to occur. In addition, the micron-level fillers in traditional insulation paper are unevenly distributed and cannot fully fill the gaps between fibers, resulting in a decrease in the heat resistance and electrical properties of the material. When the thickness of the single-layer structure paper is high, delamination or bubbles are prone to occur inside, further affecting the uniformity of the material performance.

[0004] In summary, in view of the shortcomings of aramid insulation paper in terms of anti-aging and structural stability, it has become an inevitable trend to develop new insulation paper with higher thermal stability and anti-aging properties. Summary of the invention

[0005] The invention provides an aramid insulation paper with anti-aging and high thermal stability and a preparation method thereof, solving the technical problem of how to improve the anti-aging and thermal stability of the aramid insulation paper.

[0006] The first aspect of the present invention provides an aramid insulation paper with anti-aging and high thermal stability, which is composed of a composite outer layer and an aramid inner layer;

[0007] The composite outer layer comprises unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, the aramid inner layer comprises unmodified meta-aramid fiber, and the nano-composite slurry is nano-titanium dioxide composite slurry.

[0008] Optionally, the aramid fibers used in the unmodified meta-aramid fibers and the amino-modified meta-aramid fibers are both meta-aramid chopped fibers.

[0009] Optionally, the content of the aramid fiber accounts for 50-70% of the mass of the aramid insulation paper.

[0010] Optionally, the amino-modified meta-aramid fiber is obtained by surface-modifying an amino compound in an amination reagent in the meta-aramid fiber graft modification solution;

[0011] The ratio of the mass of the amino compound to the mass of the meta-aramid fiber is (0.5-1.5):10.

[0012] Optionally, the modified solution amination reagent is a 3-aminopropyltriethoxysilane reagent solution with a concentration of 0.1-5%.

[0013] Optionally, the nanocomposite slurry is made of nano titanium dioxide and sodium dodecyl sulfate dispersant;

[0014] The mass content of the nano titanium dioxide accounts for 3-7% of the total mass of the outer layer material of the aramid insulation paper;

[0015] The particle size of the nano titanium dioxide is 20-50 nm.

[0016] Optionally, the apparent density of the composite outer layer is 20-35 g / m², and the apparent density of the aramid inner layer is 50-65 g / m².

[0017] Optionally, the thickness ratio of the composite outer layer to the aramid inner layer is 1:(8-10).

[0018] Optionally, the length of the meta-aramid chopped fibers is 3-5 mm, and the wire diameter is 5-15 µm.

[0019] A second aspect of the present invention provides a method for preparing the aramid insulation paper with anti-aging and high thermal stability, comprising:

[0020] An outer layer composite slurry is prepared based on unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, and the unmodified meta-aramid fiber is pulped to obtain an inner layer aramid slurry;

[0021] Firstly, the inner layer of aramid pulp is pumped out to the forming net through a multi-layer stepped structure die to obtain the inner layer of the wet paper blank, and then the outer layer of composite pulp is pumped out to combine with the inner layer of the wet paper blank to obtain a double-layer composite fiber paper blank;

[0022] After drying, hot pressing and constant temperature and humidity treatment of the double-layer composite fiber paper blank, aramid insulation paper with anti-aging and high thermal stability is prepared.

[0023] Optionally, the outer layer composite slurry is prepared based on unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, comprising:

[0024] The aqueous ethanol and deionized water are mixed to prepare an ethanol-water solution;

[0025] Adding aminosilane into the ethanol-water solution and stirring to mix, thereby preparing a modified solution amination reagent;

[0026] The short fibers cut from the aramid fibers are immersed in a modification solution of an amination reagent for surface modification until the pH value of the waste liquid is neutral, and then dried to obtain amino-modified meta-aramid fibers;

[0027] The amino-modified meta-aramid fiber and the unmodified meta-aramid fiber are mixed and added into deionized water for pulping to prepare a fiber mixed pulp;

[0028] The nano-composite slurry and the fiber mixed slurry are mixed and beaten, and then filtered through a screen to obtain an outer layer composite slurry.

[0029] Optionally, the method of first pumping out the inner layer of aramid slurry into the forming net through the multi-layer stepped structure mold to obtain the inner layer of the wet paper blank, and then pumping out the outer layer of composite slurry to combine with the inner layer of the wet paper blank to obtain a double-layer composite fiber paper blank comprises:

[0030] The prepared inner layer aramid slurry and outer layer composite slurry are respectively sucked into a multi-layer stepped structure mold;

[0031] The inner layer of aramid slurry is first pumped out to the forming net through a multi-layer stepped structure mold, and vacuum dehydrated to obtain the inner layer of the wet paper blank;

[0032] The outer layer of composite pulp is pumped out through a multi-layer stepped structure mold and combined with the inner layer of the wet paper blank in a forming net to produce a double-layer composite fiber paper blank with a continuous fiber network structure;

[0033] Among them, the ratio of the thickness of the inner layer aramid slurry pumped out through the multi-layer stepped structure mold to the thickness of the outer layer composite slurry pumped out is 1: (8-10).

[0034] Optionally, the double-layer composite fiber paper blank is dried, hot pressed and subjected to constant temperature and humidity treatment to obtain aramid insulation paper with anti-aging and high thermal stability, comprising:

[0035] The double-layer composite fiber paper blank is subjected to a graded and progressive heating and drying treatment;

[0036] Cutting the double-layer composite fiber paper blank after drying;

[0037] The cut double-layer composite fiber paper blank is subjected to heat pressing treatment;

[0038] The double-layer composite fiber paper blank after heat pressing is subjected to constant temperature and humidity treatment to obtain aramid insulation paper with anti-aging and high thermal stability.

[0039] It can be seen from the above technical solutions that the present invention has the following advantages:

[0040] The present invention introduces amino-modified meta-aramid fiber (AF-AMF) treated with amino modification, combines unmodified meta-aramid fiber and nano-composite slurry to form a composite outer layer of aramid insulation paper. Through amino modification, active amino functional groups are introduced into the surface of aramid fiber to enhance the interfacial bonding force between fiber and filler and other fibers. The dispersion and uniformity of the fiber are improved, the problem of traditional fiber agglomeration is avoided, and the overall mechanical properties of the paper are enhanced, especially the interlayer bonding strength and tear resistance. Through nano titanium dioxide ( ) The introduction of reinforcing materials provides aramid insulation paper with excellent heat resistance and electrical insulation properties. Functional stratification is achieved by using unmodified meta-aramid fibers as the main inner layer and unmodified fibers, modified fibers and nanofillers as the outer layer: the inner layer provides high mechanical strength and the outer layer provides excellent electrical insulation properties. The overall flexibility of the paper is guaranteed to adapt to complex deformation requirements. The double-layer structure is integrally formed by wet papermaking to ensure seamless bonding between layers. It eliminates the problems of bubbles or stratification that may exist in traditional hot-pressed lamination. It reduces the thickness difference of paper and improves the consistency of finished products. It solves the technical problem of how to improve the anti-aging and thermal stability of aramid insulation paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0042] Figure 1This is a schematic structural diagram of the aramid insulation paper with anti-aging and high thermal stability according to an embodiment of the present invention;

[0043] Figure 2 It is a schematic diagram of the three-dimensional structure of a multi-layer stepped structure mold according to an embodiment of the present invention;

[0044] Figure 3 It is an analytical diagram of preparing a multi-layer stepped structure mold according to an embodiment of the present invention;

[0045] Figure 4 The present invention is a flowchart of a method for preparing aramid insulation paper with high thermal stability and anti-aging properties according to an embodiment of the present invention. DETAILED DESCRIPTION

[0046] The embodiment of the present invention provides an aramid insulation paper with anti-aging and high thermal stability and a preparation method thereof, which are used to solve the technical problem of how to improve the anti-aging and thermal stability of the aramid insulation paper.

[0047] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The present invention relates to a composite aramid insulation paper with anti-aging and high thermal stability and a preparation method thereof. Through innovative design and process improvement, the mechanical and electrical properties of the material are significantly enhanced. The insulation paper adopts a double-layer thickness gradient distribution structure. The outer layer is composed of unmodified meta-aramid fiber, amino-modified meta-aramid fiber (AF-AMF) and nano-aramid fiber. Made of composite slurry, the inner layer is unmodified meta-aramid fiber, giving full play to the structural and functional layering advantages of the material. Among them, the outer layer provides excellent electrical insulation performance and thermal stability, and the inner layer is mainly responsible for enhancing mechanical strength. Through wet process one-piece molding, it ensures seamless combination between the two layers, effectively avoiding problems such as bubbles and stratification that are prone to occur in traditional hot pressing lamination process.

[0049] The present invention introduces active amino functional groups on the surface of aramid fiber through amino modification treatment, thereby enhancing the interfacial bonding between fiber, filler and other fibers. It improves the dispersion and uniformity of fiber, avoids the problem of traditional fiber agglomeration, and enhances the overall mechanical properties of paper, especially the interlayer bonding strength and tear resistance. Nano titanium dioxide ( ) The introduction of reinforcing materials provides excellent heat resistance and electrical insulation properties for the insulation paper. During the filler processing, SDS dispersant is added to further stabilize the filler dispersion. Ultrasonic dispersion treatment is used to ensure that the nano The uniform distribution in the slurry further enhances the interfacial bonding between the filler and the amino-modified aramid fiber, reduces the thermal expansion coefficient of the paper, and improves its dimensional stability. The fine particle size of the filler (20-50 nm) further optimizes the breakdown voltage performance and arc resistance of the paper.

[0050] Functional stratification is achieved by using unmodified aramid fibers as the main inner layer and modified fibers and nanofillers as the outer layer: the inner layer provides high mechanical strength and the outer layer provides excellent electrical insulation. Therefore, the outer layer thickness is designed to be thin to meet functional requirements. An overly thick outer layer not only increases material costs, but may also reduce flexibility and the ability to adapt to complex mechanical deformations. The main task of the inner layer is to provide mechanical strength and support, and a significantly thicker ratio is required to ensure the stability and durability of the overall structure. The outer layer contains amino-modified aramid fibers and nanofillers. Fillers, these materials are relatively expensive, and if the thickness of the outer layer is too large, the material cost will be significantly increased. The thickness of the outer layer needs to be moderate to provide electrical insulation performance, while the inner layer needs to be thicker to provide mechanical support. This requirement directly leads to a thickness design of 1: (8-10). The thickness ratio of 1: (8-10) can not only meet performance requirements, but also optimize the cost structure, making the material distribution more economical and reasonable. This ratio is the best choice based on the trade-off between performance optimization and economic efficiency. Ensure the overall flexibility of the paper and adapt to complex deformation requirements. The double-layer structure is formed in one piece through wet papermaking to ensure seamless bonding between layers. It eliminates the problems of bubbles or delamination that may exist in traditional hot pressing lamination. Reduce paper thickness differences and improve finished product consistency.

[0051] See also Figure 1-Figure 3 , the present invention provides an aramid insulation paper with anti-aging and high thermal stability, which is composed of a composite outer layer and an aramid inner layer;

[0052] The composite outer layer includes unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, the aramid inner layer includes unmodified meta-aramid fiber, and the nano-composite slurry is nano-titanium dioxide composite slurry.

[0053] For easier understanding, see Figure 1 ,In the figure, 1 is the composite outer layer, and 2 is the aramid inner layer.

[0054] The present invention introduces amino-modified meta-aramid fiber (AF-AMF) treated with amino modification, combines unmodified meta-aramid fiber and nano-composite slurry to form a composite outer layer of aramid insulation paper. Through amino modification, active amino functional groups are introduced into the surface of aramid fiber to enhance the interfacial bonding force between fiber and filler and other fibers. The dispersion and uniformity of the fiber are improved, the problem of traditional fiber agglomeration is avoided, and the overall mechanical properties of the paper are enhanced, especially the interlayer bonding strength and tear resistance. Through nano titanium dioxide ( ) The introduction of reinforcing materials provides aramid insulation paper with excellent heat resistance and electrical insulation properties. Functional stratification is achieved by using unmodified meta-aramid fibers as the main inner layer and unmodified fibers, modified fibers and nanofillers as the outer layer: the inner layer provides high mechanical strength and the outer layer provides excellent electrical insulation properties. The overall flexibility of the paper is guaranteed to adapt to complex deformation requirements. The double-layer structure is integrally formed by wet papermaking to ensure seamless bonding between layers. It eliminates the problems of bubbles or stratification that may exist in traditional hot-pressed lamination. It reduces the thickness difference of paper and improves the consistency of finished products. It solves the technical problem of how to improve the anti-aging and thermal stability of aramid insulation paper.

[0055] The present invention provides an aramid insulation paper with anti-aging and high thermal stability, wherein the aramid fibers used in the unmodified meta-aramid fibers and the amino-modified meta-aramid fibers are both meta-aramid chopped fibers;

[0056] The length of meta-aramid chopped fibers is 3-5 mm and the fiber diameter is 5-15 µm.

[0057] It should be noted that the aramid fibers used in the unmodified meta-aramid fibers and the amino-modified meta-aramid fibers are both meta-aramid chopped fibers, which have a length of 3-5 mm and a wire diameter of 5-15 µm. Meta-aramid chopped fibers are easy to mix and form, and have good fluidity. The requirements for equipment during processing are relatively low. At the same time, meta-aramid fibers themselves have excellent thermal stability and can maintain good physical and chemical properties in high temperature environments. When meta-aramid chopped fibers are used to reinforce materials, the chopped fibers can increase the thermal decomposition temperature of the material, reduce the thermal expansion coefficient of the material at high temperatures, and make the material have better dimensional stability in high temperature environments.

[0058] The following is a specific test example 1:

[0059] In this test example, standard meta-aramid short-cut fibers were used, with a short-cut fiber length of 3-5 mm and a fiber diameter of 5-15 μm. No amino treatment was performed, and no nanoparticles were added. During the wet papermaking process, the slurry flow rate control was relatively loose, the breakdown voltage strength of the final product was 17 kV / mm, and the thermal aging performance retention rate was 63%.

[0060] Comparative Example 1 uses standard meta-aramid short-cut fibers with a length of 3-5 mm and a diameter of 8-12 μm, without amino treatment and without adding nano During the wet papermaking process, the slurry flow rate control is relatively loose, the breakdown voltage strength of the final product is 15 kV / mm, and the thermal aging performance retention rate is 62%, which is slightly lower than the composite aramid insulation paper of the present invention.

[0061] Comparative Example 2 Aramid short-cut fibers have a length of 6-8 mm and a wire diameter of 5-15 μm, are not subjected to amino treatment, and are not added with nanoparticles. During the wet papermaking process, the slurry flow rate control is relatively loose, the breakdown voltage strength of the final product is 14 kV / mm, and the thermal aging performance retention rate is 58%, which is slightly lower than the composite aramid insulation paper of the present invention.

[0062] Table 1. Test results

[0063]

[0064] The fibers of Example 1 and Comparative Example 1 are shorter and thinner, have better fluidity, and are suitable for low-demand processing environments, while the fibers of Comparative Example 2 are longer and may have higher processing requirements. In terms of performance, the breakdown voltage and thermal aging performance of Example 1 are better than those of Comparative Examples 1 and 2, indicating that shorter and smaller diameter fibers exhibit better thermal stability and electrical properties in high temperature environments.

[0065] The invention provides aramid insulation paper with anti-aging and high thermal stability, wherein the content of aramid fiber accounts for 50-70% of the paper.

[0066] It should be noted that the content of aramid fiber accounts for 50-70% of the mass of aramid insulation paper, which can provide a strong supporting skeleton for the paper, greatly enhancing the paper's ability to resist external tensile force, toughness and tear resistance.

[0067] Furthermore, when aramid fiber accounts for 50-70% of the paper, the overall thermal decomposition temperature of the insulating paper will be significantly increased, and it is not easy to soften, deform or burn under high temperature conditions. At the same time, aramid fiber itself has good flame retardancy, and its molecular structure contains flame retardant elements, which can prevent the propagation and spread of flames during the combustion process.

[0068] The present invention provides an aramid insulation paper with anti-aging and high thermal stability, wherein the amino-modified meta-aramid fiber is prepared by surface modification of an amino compound in an amination reagent of a meta-aramid fiber graft modification solution;

[0069] The ratio of the mass of the amino compound to the mass of the meta-aramid fiber is (0.5-1.5):10.

[0070] The modified solution amination reagent is a 3-aminopropyltriethoxysilane reagent solution with a concentration of 0.1-5%.

[0071] It should be noted that the amino-modified meta-aramid fiber is achieved by grafting amino compounds on the surface. The ratio of the mass of the amino compound to the mass of the aramid fiber is (0.5-1.5):10. The amination reagent of the modification solution is a 3-aminopropyltriethoxysilane reagent solution with a concentration of 0.1-5%. The meta-aramid fiber is surface-modified by a 3-aminopropyltriethoxysilane (APTES) reagent solution with a concentration of 0.1-5%.

[0072] The following is a specific test example 2:

[0073] In this test example, the aramid fiber used is meta-aramid chopped fiber, the chopped fiber length is 3-5 mm, and the fiber diameter is 8-12 μm. The surface is treated with amino to enhance the bonding strength with the aramid fiber. During the wet papermaking process, the slurry flow rate control is relatively loose, and the breakdown voltage strength of the final product is 18 kV / mm, and the thermal aging performance retention rate is 69%.

[0074] Comparative Example 3 uses standard meta-aramid short-cut fibers with a length of 3-5 mm and a diameter of 8-12 μm, without amino treatment and without adding nano During the wet papermaking process, the slurry flow rate control is relatively loose, the breakdown voltage strength of the final product is 15 kV / mm, and the thermal aging performance retention rate is 60%, which is lower than the composite aramid insulation paper of the present invention.

[0075] Comparative Example 4 uses standard meta-aramid short-cut fibers with a length of 3-5 mm and a diameter of 8-12 μm. The surface is treated with amino to enhance the bonding strength with aramid fibers. No nanoparticles are added. During the wet papermaking process, the slurry flow rate control is relatively loose, the breakdown voltage strength of the final product is 17 kV / mm, and the thermal aging performance retention rate is 65%, which is lower than the composite aramid insulation paper of the present invention.

[0076] Table 2. Test results

[0077]

[0078] The electrical properties and thermal stability of amino-modified meta-aramid fiber are significantly improved through surface amino modification, especially in terms of high breakdown voltage and thermal aging performance.

[0079] The present invention provides an aramid insulation paper with anti-aging and high thermal stability, wherein the nano-composite slurry is made of nano-titanium dioxide and sodium dodecyl sulfate dispersant;

[0080] The mass content of nano-titanium dioxide accounts for 3-7% of the total mass of the outer layer material of aramid insulation paper;

[0081] The particle size of nano titanium dioxide is 20-50 nm.

[0082] It should be noted that the nanocomposite slurry is made of nano titanium dioxide and sodium dodecyl sulfate dispersant. During the filler processing, SDS dispersant is added to further stabilize the filler dispersion. Ultrasonic dispersion treatment is used to ensure that the nanocomposite slurry is stable. The uniform distribution in the slurry further enhances the interfacial bonding between the filler and the amino-modified aramid fiber, reduces the thermal expansion coefficient of the paper, and improves its dimensional stability. The fine particle size of the filler (20-50 nm) further optimizes the breakdown voltage performance and arc resistance of the paper.

[0083] It should be noted that the mass content of nano-titanium dioxide accounts for 3-7% of the total mass of the outer material of aramid insulation paper. When the mass content of nano-titanium dioxide in the material is 3% - 7%, it can effectively absorb and shield ultraviolet rays, reduce the damage of ultraviolet rays to the internal structure of the material and the protected material, thereby preventing photochemical reactions caused by ultraviolet rays, such as material aging. At the same time, when the mass content is 3% - 7%, nano-titanium dioxide particles are evenly dispersed in the material, which can play a role of filling and strengthening, and improve the mechanical properties of the material, such as tensile strength, bending strength, etc. It plays a role in anti-aging and enhancing the strength of the material.

[0084] The invention provides an aramid insulation paper with anti-aging and high thermal stability, wherein the apparent density of the composite outer layer is 20-35 g / m², and the apparent density of the aramid inner layer is 50-65 g / m².

[0085] It should be noted that the apparent density of the composite outer layer is relatively low, which means that the structure of the outer insulation paper is relatively loose and contains more air gaps. Air itself is a good insulating medium, and these air gaps can further enhance the insulation performance of the insulation paper. When the insulation paper is subjected to external mechanical stress, the loose structure of the outer layer can absorb and disperse part of the energy, reducing damage to the inner insulation paper and internal electrical components. At the same time, the low-density structure of the outer insulation paper allows air to flow through it, which is conducive to the conduction and dissipation of heat.

[0086] The higher apparent density of the aramid inner layer makes its structure more compact, the arrangement of fibers more closely, and the reduction of internal pores and defects. This dense structure can effectively prevent the leakage and penetration of charges, providing more reliable insulation protection for internal electrical components. At the same time, the higher apparent density can prevent heat from being transferred from the internal electrical components to the outer layer too quickly to a certain extent. This thermal insulation effect can keep the internal electrical components at a relatively stable temperature during operation, avoiding the impact of excessive temperature fluctuations on their performance.

[0087] The present invention provides an aramid insulation paper with anti-aging and high thermal stability, wherein the thickness ratio of the composite outer layer to the aramid inner layer is 1: (8-10).

[0088] It should be noted that an overly thick outer layer not only increases material costs, but may also reduce flexibility and the ability to adapt to complex mechanical deformations. The main task of the inner layer is to provide mechanical strength and support, and it needs to be significantly thicker to ensure the stability and durability of the overall structure. The outer layer contains amino-modified aramid fibers and nano Fillers, these materials are expensive, and if the outer layer thickness is too large, it will significantly increase the material cost. The outer layer thickness needs to be moderate to provide electrical insulation performance, while the inner layer needs to be thicker to provide mechanical support. This requirement directly leads to a thickness design of 1: (8-10). The thickness ratio of 1: (8-10) can not only meet performance requirements, but also optimize the cost structure, making the material distribution more economical and reasonable. This ratio is the best choice based on the trade-off between performance optimization and economic efficiency.

[0089] In an embodiment of the present invention, aramid insulation paper is prepared by a specific multi-layer stepped structure mold, so that the thickness ratio of the composite outer layer to the aramid inner layer is 1: (8-10), the outer layer and the inner layer present a gradually changing design in physical properties and material composition, and the thickness distribution is gradient, rather than just the traditional simple two-layer superposition, which can not only meet performance requirements, but also optimize the cost structure, making the material distribution more economical and reasonable.

[0090] See also Figure 2-Figure 4 The present invention provides a method for preparing aramid insulation paper with anti-aging and high thermal stability, comprising:

[0091] Step 101: prepare an outer layer composite slurry based on unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, and beat the unmodified meta-aramid fiber to obtain an inner layer aramid slurry.

[0092] Step 102: firstly pump out the inner layer of aramid slurry into the forming net through the multi-layer stepped structure mold to obtain the inner layer of the wet paper blank, and then pump out the outer layer of composite slurry to combine with the inner layer of the wet paper blank to obtain a double-layer composite fiber paper blank.

[0093] Step 103, drying, hot pressing and constant temperature and humidity treatment are performed on the double-layer composite fiber paper blank to obtain aramid insulation paper with anti-aging and high thermal stability.

[0094] In an embodiment of the present invention, unmodified meta-aramid fibers are beaten by a mechanical beater to form an inner layer of aramid slurry, short fibers cut from the aramid fibers are immersed in a modified solution aminating agent, and the fibers are mixed at a given mass ratio to prepare amino-modified meta-aramid fibers (AF-AMF), amino-modified meta-aramid fibers, unmodified meta-aramid fibers and nano-titanium dioxide dispersion are mixed at a given mass ratio, and are fully dispersed by mechanical stirring to form an outer layer of multifunctional composite slurry (fiber mixed slurry), the inner layer of aramid slurry is first pumped out into a forming net through a multi-layer stepped structure mold to obtain an inner layer of a wet paper blank, and then the outer layer of composite slurry is pumped out to combine with the inner layer of the wet paper blank to obtain a double-layer composite fiber paper blank, and the double-layer composite fiber paper blank is dried, hot pressed and subjected to constant temperature and humidity treatment to obtain aramid insulation paper with anti-aging and high thermal stability.

[0095] Furthermore, step 101 may include the following sub-steps:

[0096] S11, mixing aqueous ethanol and deionized water to prepare an ethanol-water solution.

[0097] S12, adding aminosilane into the ethanol-water solution and stirring to mix, so as to obtain a modified solution amination reagent.

[0098] S13, immersing the short fibers cut from the aramid fibers into a modification solution of an amination reagent for surface modification until the pH value of the waste liquid becomes neutral, and then drying to obtain amino-modified meta-aramid fibers.

[0099] S14, mixing the amino-modified meta-aramid fiber with the unmodified meta-aramid fiber, adding the mixture into deionized water for pulping, and preparing a fiber mixed pulp.

[0100] S15, mixing and beating the nano-composite slurry and the fiber mixed slurry, and filtering through a sieve to obtain an outer layer composite slurry.

[0101] In an embodiment of the present invention, aqueous ethanol and deionized water are mixed to prepare an ethanol-water solution, the ethanol-water solution is used as an amination reaction solution, aramid fibers are cut into short fibers with a length of 3-5 mm, aminosilane is added to the ethanol-water solution at a ratio of 0.5-1.5 times the mass of the fiber, and stirred evenly to prepare a modified solution amination reagent, the concentration of which is controlled at 0.5-1 wt%, and the modified solution amination reagent is a 0.1-5% 3-aminopropyltriethoxysilane reagent solution, and then the cut short fibers are immersed in the modified solution amination reagent, placed in a constant temperature water bath, the temperature is controlled at 40-60°C, the reaction time is 1.5 hours, and stirring is maintained to ensure that the fiber surface is fully in contact with the modified solution amination reagent. After the reaction is completed, the fiber is rinsed with deionized water for several times until the pH value of the waste liquid is neutral. Finally, the rinsed fiber is dried at 80-100°C for 4-6 hours to obtain amino-modified meta-aramid fiber (AF-AMF). The amino-modified meta-aramid fiber and the unmodified meta-aramid fiber are mixed in a mass ratio of 8:2 and added into an appropriate amount of deionized water. After being de-pulped by a standard fiber de-pulper at 12000-18000 r, a high-speed beater is used to beat the fiber at a speed of 16000-20000 rpm for 15-20 min to finally obtain a fiber mixed slurry. Nanoparticles subjected to ultrasonic dispersion treatment are added into the fiber mixed slurry. (ultrasonic power 100 W, lasting 10 minutes), the addition amount is 3-7% of the total mass of the slurry, and SDS dispersant (dispersant content is Use a high-speed disperser to stir for 30 minutes at a speed of 3000-5000 rpm to ensure that the fibers are Mix thoroughly. Filter the slurry through a 200-mesh screen to ensure that the slurry does not contain large particles or impurities that are not evenly dispersed. Finally, the outer layer composite slurry is obtained.

[0102] Further, step 102 may include the following sub-steps:

[0103] S21. The prepared inner layer aramid slurry and outer layer composite slurry are respectively sucked into two syringes connected to the corresponding feed ports of the multi-layer stepped structure mold.

[0104] S22, first pumping out the inner layer of aramid slurry into the forming net through a multi-layer stepped structure mold, and performing vacuum dehydration to obtain the inner layer of the wet paper blank.

[0105] S23, pumping out the outer layer of composite slurry through a multi-layer stepped structure mold, and combining it with the inner layer of the wet paper blank in a forming net to produce a double-layer composite fiber paper blank with a continuous fiber network structure;

[0106] Among them, the ratio of the thickness of the inner layer aramid slurry pumped out through the multi-layer stepped structure mold to the thickness of the outer layer composite slurry pumped out is 1: (8-10).

[0107] It should be noted that the multi-layer stepped structure mold is specifically a three-layer stepped structure mold, and the n+1-layer stepped structure mold is set specifically according to the number of layers n of the insulating paper. The lower sizing port is coaxially arranged with the discharge port of the inner layer aramid slurry, and is directly below the lower sizing port; the upper sizing port is coaxially arranged with the discharge port of the outer layer composite slurry, and is directly below the upper sizing port.

[0108] For easier understanding, see Figure 2-Figure 3 In the figure, 3 is a double-layer composite aramid insulation paper, 4 is a syringe, and 5 is a multi-layer ladder structure mold. Figure 3 The dotted line in the figure is the forming mesh.

[0109] In the embodiment of the present invention, the prepared inner layer aramid slurry and outer layer composite slurry are respectively sucked into two syringes connected to the corresponding feed ports of the multi-layer stepped structure mold, and the seal is checked and ensured to be tight. The power pump on the syringe is placed in the running mode, and the pumping rate of each syringe is adjusted to make the ratio of the pumping rate of the syringe corresponding to each layer of material consistent with the ratio of the thickness between the layers of material. First, the inner layer aramid slurry is injected into the forming net from the lower slurry port through the multi-layer stepped structure mold to first complete the preliminary forming of the inner layer, and the wet paper reaches a certain humidity through vacuum dehydration. , controlled at 50%-60%, maintaining the stability of the wet structure, worthy of the inner layer of the wet paper blank, at this time the inner layer of the wet paper blank has not been completely solidified, providing conditions for the attachment of the outer layer of composite pulp, the outer layer of composite pulp is injected from the sizing port through the multi-layer stepped structure mold, and directly contacts with the inner layer of the wet paper blank in the forming net. Since the inner layer of the wet paper blank is in a wet state, its surface fibers are loose and can be well combined with the fibers and fillers in the outer layer of composite pulp. Through moderate gravity and mechanical force, the fibers of the two layers of pulp are staggered and combined at the junction to form a continuous fiber network structure.

[0110] It is worth mentioning that the feed ports (upper slurry port and lower slurry port) of the multi-layer stepped structure mold of the present invention are used for injecting the outer layer slurry and the inner layer slurry, respectively, to ensure the independent flow and distribution of the slurries in different layers.

[0111] The slurry pumping rate is controlled by an injection pump, replacing the simple gravity flow of the traditional headbox, and the distribution ratio of each layer of slurry is accurately adjusted.

[0112] The forming net replaces the traditional papermaking net. The forming net focuses more on the actual load-bearing part used to support and guide pulp forming during the papermaking process. The forming net can better control the fiber distribution and arrangement of the wet paper sheet, so that the fibers are more evenly distributed and interwoven in the paper, forming a double-layer composite fiber paper blank with a continuous fiber network structure. This optimized fiber structure can improve the strength and toughness of the paper, making it less likely to break and damage during use. In addition, the good dehydration performance of the forming net also helps to maintain the integrity and bonding of the fibers, further enhancing the physical properties of the paper.

[0113] Further, step 103 may include the following sub-steps:

[0114] S31, performing a stepwise heating and drying process on the double-layer composite fiber paper blank;

[0115] S32, cutting the double-layer composite fiber paper blank after drying;

[0116] S33, performing heat pressing treatment on the cut double-layer composite fiber paper blank;

[0117] S33. The double-layer composite fiber paper blank after the heat pressing treatment is subjected to a constant temperature and humidity treatment to obtain an aramid insulation paper with anti-aging and high thermal stability.

[0118] In an embodiment of the present invention, the double-layer composite fiber paper blank is subjected to a step-by-step heating and drying treatment, that is, the moisture in the double-layer composite fiber paper blank is gradually evaporated through a step-by-step heating drying system. The initial drying temperature is controlled at 80-100°C, and the drying time is 20-30 min to avoid shrinkage and deformation of the paper. The drying temperature in the final stage is raised to 120-150°C, and the drying time is 20-30 min to ensure complete drying. The double-layer composite fiber paper blank after drying is cut to a standard size, stacked in a hot pressing mold, and hot-pressed at a given temperature and pressure, that is, hot-pressed at a temperature of 260-300°C and a pressure of 15-25 MPa for 10-20 minutes. After hot pressing, the temperature is controlled between 260-300, the pressure is controlled between 15-25 MPa, and the time is controlled between 10-20 minutes. It is characterized in that the breakdown voltage strength is not less than 25 kV / mm in an environment of 180°C. In the thermal aging performance test, after continuous aging at 200°C for 1000 hours, the thermal aging performance retention rate was higher than 80%. The double-layer composite fiber paper blank after hot pressing was subjected to constant temperature and humidity treatment, that is, it was placed in a constant temperature and humidity chamber with the conditions set at 25±2°C and relative humidity of 60%-70%. The constant temperature and humidity treatment was performed for 24-48 hours to obtain aramid insulation paper with anti-aging and high thermal stability.

[0119] The following are specific test examples:

[0120] In this test example, the aramid fiber used is meta-aramid short-cut fiber, the short-cut fiber length is 3-5 mm, and the fiber diameter is 8-12 μm. The particles have good dispersibility, with a particle size of 20-50 nm, and the surface is treated with amino to enhance the bonding with aramid fibers. Finally, through step-by-step drying and hot pressing at 260°C and 20 MPa, the composite aramid insulation paper with optimized heat resistance and mechanical properties is prepared.

[0121] Comparative Example 5 uses standard meta-aramid short-cut fibers with a length of 3-5 mm and a diameter of 8-12 μm, without amino treatment and without adding nano During the wet papermaking process, the slurry flow rate control is relatively loose, the breakdown voltage strength of the final product is 15 kV / mm, and the thermal aging performance retention rate is 60%, which is much lower than the composite aramid insulation paper of the present invention.

[0122] Comparative Example 6 uses aramid short-cut fibers with a length of 3-5 mm and a diameter of 8-12 μm. It is not amino-modified, but uses a conventional filler addition method. The filler is a nanoparticle with a larger particle size. (50-100 nm), with a mass content of 2%-4%. The traditional wet papermaking process was used, but the precise multi-layer stepped structure mold was not used.

[0123] Table 3. Test results

[0124]

[0125] Compared with the composite aramid insulation paper in Comparative Example 2, the breakdown voltage strength of the present invention can reach 25 kV / mm at 180°C, while the breakdown voltage strength of Comparative Example 2 is only 18 kV / mm, and after continuous aging at 200°C for 1000 hours, the thermal aging performance retention rate of the present invention is as high as more than 80%, while the thermal aging performance retention rate of Comparative Example 2 is only 65%-70%, showing obvious attenuation. In terms of dimensional stability, the present invention ensures the excellent anti-deformation performance of the material through a double-layer gradient structure design, while the material of Comparative Example 2 is prone to deformation caused by thermal expansion. In addition, the production process of the present invention adopts a multi-layer ladder structure mold to ensure the uniformity of each layer of slurry and the interlayer bonding force, while the traditional wet papermaking process of Comparative Example 2 has obvious deficiencies in slurry uniformity and interlayer bonding force.

[0126] The present invention provides a multifunctional composite aramid insulation paper with both heat resistance and mechanical properties and a preparation method thereof. The composite aramid insulation paper uses high-strength aramid fiber as a reinforcement skeleton and combines nano The surface modified functional elements of the particles systematically solve the bottleneck problem of traditional insulation paper in the coordinated optimization of heat resistance and mechanical properties. The present invention proposes to use unmodified meta-aramid fiber as the inner layer support structure, amino-modified aramid fiber, unmodified meta-aramid fiber and nano The composite layer is the outer protective barrier. Through the double-layer wet papermaking combined with the step-by-step hot pressing process, a double-layer composite aramid insulation paper is constructed, which significantly improves the synergistic effect of heat resistance and mechanical strength. Compared with traditional aramid insulation paper, the breakdown voltage strength of the product of the present invention is increased to 25-28 kV / mm, and the thermal aging performance retention rate is >85%. Overall, the composite aramid insulation paper of the present invention exhibits excellent performance in electrical properties, thermal stability, mechanical strength and production efficiency, and is suitable for demanding electrical equipment fields. It is also suitable for fields such as new energy vehicles and high-speed railways, and meets the high performance requirements for insulation materials of electrical equipment under high temperature and high humidity environments. The preparation method provided by the present invention has the advantages of simple operation, high paper quality, low labor intensity, etc., and has good potential for upgrading to industrial production.

[0127] The method for preparing the composite aramid insulation paper with coordinated optimization of heat resistance and mechanical properties may include the following steps:

[0128] First, the fiber was modified and an amination reaction solution was prepared. Ethanol and deionized water were mixed in a volume ratio of 7:3 as the base liquid, and APTES (mass ratio to aramid fiber 1:10) was added. After sufficient stirring, the meta-aramid fiber sheared to 5 mm was immersed in the solution. The fiber was reacted in a 50°C constant temperature water bath for 1.5 hours with continuous stirring. The fiber was then rinsed with deionized water until neutral and dried at 80°C for 5 hours to obtain amino-modified meta-aramid fiber (AF-AMF). The inner layer slurry was prepared using unmodified meta-aramid fiber, which was made into a slurry with a fiber concentration of 5% after mechanical beating. The outer layer composite slurry was prepared by mixing amino-modified meta-aramid fiber and unmodified meta-aramid fiber in a mass ratio of 8:2, combined with nano-particles treated with ultrasonic dispersion. , add 0.05% SDS dispersant, disperse by ultrasound for 10 minutes and stir, then filter through a 200-mesh screen to form a uniform slurry. In the double-layer composite paper forming stage, the inner layer slurry is first injected into the surface of the forming net through a wet papermaking process, dehydrated to a humidity of 55%, and then injected into the outer layer slurry, so that the two layers are combined in a wet state to form a double-layer structure with an interlaced fiber network. After forming, the material is initially dried at 100°C for 30 minutes, then heated to 150°C and dried for 30 minutes; then hot pressed at 260°C and a pressure of 20 MPa for 15 minutes to set the shape. Finally, the hot-pressed aramid paper is placed in a constant temperature and humidity chamber at 25°C and a humidity of 65% for 36 hours to ensure stable performance.

[0129] Those skilled in the art can clearly understand that, for the convenience and brevity of description, the specific working processes of the systems, devices and units described above can refer to the corresponding processes in the aforementioned method embodiments and will not be repeated here.

[0130] In the several embodiments provided in the present application, it should be understood that the disclosed systems, devices and methods can be implemented in other ways. For example, the device embodiments described above are only schematic. For example, the division of the units is only a logical function division. There may be other division methods in actual implementation, such as multiple units or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be an indirect coupling or communication connection through some interfaces, devices or units, which can be electrical, mechanical or other forms.

[0131] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An aramid insulation paper with anti-aging and high thermal stability, characterized in that: It is composed of a composite outer layer and an aramid inner layer; The composite outer layer comprises unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, the aramid inner layer comprises unmodified meta-aramid fiber, and the nano-composite slurry is nano-titanium dioxide composite slurry.

2. The aramid insulation paper with anti-aging and high thermal stability according to claim 1, characterized in that: The aramid fibers used in the unmodified meta-aramid fibers and the amino-modified meta-aramid fibers are both meta-aramid chopped fibers.

3. The aramid insulation paper with anti-aging and high thermal stability according to claim 2, characterized in that: The content of the aramid fiber accounts for 50-70% of the mass of the aramid insulation paper.

4. The aramid insulation paper with anti-aging and high thermal stability according to claim 2, characterized in that: The amino-modified meta-aramid fiber is obtained by surface-modifying the amino compound in the amination reagent of the meta-aramid fiber graft modification solution; The ratio of the mass of the amino compound to the mass of the meta-aramid fiber is (0.5-1.5):

10.

5. The aramid insulation paper with anti-aging and high thermal stability according to claim 4, characterized in that: The modified solution amination reagent is a 3-aminopropyltriethoxysilane reagent solution with a concentration of 0.1-5%.

6. The aramid insulation paper with anti-aging and high thermal stability according to claim 1, characterized in that: The nanocomposite slurry is made of nano titanium dioxide and sodium dodecyl sulfate dispersant; The mass content of the nano titanium dioxide accounts for 3-7% of the total mass of the outer layer material of the aramid insulation paper; The particle size of the nano titanium dioxide is 20-50 nm.

7. The aramid insulation paper with anti-aging and high thermal stability according to claim 1, characterized in that: The apparent density of the composite outer layer is 20-35 g / m², and the apparent density of the aramid inner layer is 50-65 g / m².

8. The aramid insulation paper with anti-aging and high thermal stability according to any one of claims 1 to 7, characterized in that: The thickness ratio of the composite outer layer to the aramid inner layer is 1:(8-10).

9. The aramid insulation paper with anti-aging and high thermal stability according to claim 2, characterized in that: The length of the meta-aramid chopped fibers is 3-5 mm, and the wire diameter is 5-15 μm.

10. A method for preparing the aramid insulation paper with anti-aging and high thermal stability as claimed in any one of claims 1 to 9, characterized in that: include: An outer layer composite slurry is prepared based on unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, and the unmodified meta-aramid fiber is pulped to obtain an inner layer aramid slurry; Firstly, the inner layer of aramid pulp is pumped out to the forming net through a multi-layer stepped structure die to obtain the inner layer of the wet paper blank, and then the outer layer of composite pulp is pumped out to combine with the inner layer of the wet paper blank to obtain a double-layer composite fiber paper blank; After drying, hot pressing and constant temperature and humidity treatment of the double-layer composite fiber paper blank, aramid insulation paper with anti-aging and high thermal stability is prepared.

11. The preparation method according to claim 10, characterized in that: The outer layer composite slurry is prepared based on unmodified meta-aramid fiber, amino-modified meta-aramid fiber and nano-composite slurry, comprising: The aqueous ethanol and deionized water are mixed to prepare an ethanol-water solution; Adding aminosilane into the ethanol-water solution and stirring to mix, thereby preparing a modified solution amination reagent; The short fibers cut from the aramid fibers are immersed in a modification solution of an amination reagent for surface modification until the pH value of the waste liquid is neutral, and then dried to obtain amino-modified meta-aramid fibers; The amino-modified meta-aramid fiber and the unmodified meta-aramid fiber are mixed and added into deionized water for pulping to prepare a fiber mixed pulp; The nano-composite slurry and the fiber mixed slurry are mixed and beaten, and then filtered through a screen to obtain an outer layer composite slurry.

12. The preparation method according to claim 10, characterized in that: The method firstly pumps out the inner layer of aramid pulp into the forming net through the multi-layer stepped structure mold to obtain the inner layer of the wet paper blank, and then pumps out the outer layer of composite pulp to combine with the inner layer of the wet paper blank to obtain the double-layer composite fiber paper blank, including: The prepared inner layer aramid slurry and outer layer composite slurry are respectively sucked into a multi-layer stepped structure mold; The inner layer of aramid slurry is first pumped out to the forming net through a multi-layer stepped structure mold, and vacuum dehydrated to obtain the inner layer of the wet paper blank; The outer layer of composite pulp is pumped out through a multi-layer stepped structure mold and combined with the inner layer of the wet paper blank in a forming net to produce a double-layer composite fiber paper blank with a continuous fiber network structure; Among them, the ratio of the thickness of the inner layer aramid slurry pumped out through the multi-layer stepped structure mold to the thickness of the outer layer composite slurry pumped out is 1: (8-10).

13. The preparation method according to claim 10, characterized in that: After the double-layer composite fiber paper blank is dried, hot pressed and subjected to constant temperature and humidity treatment, the aramid insulation paper with anti-aging and high thermal stability is obtained, comprising: The double-layer composite fiber paper blank is subjected to a graded and progressive heating and drying treatment; Cutting the double-layer composite fiber paper blank after drying; The cut double-layer composite fiber paper blank is subjected to heat pressing treatment; The double-layer composite fiber paper blank after heat pressing is subjected to constant temperature and humidity treatment to obtain aramid insulation paper with anti-aging and high thermal stability.

Citation Information

Cited By

  • Meta-aramid chopped fiber, aramid insulation paper and preparation method

    CN120625209A